1996
DOI: 10.1161/01.cir.93.9.1747
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Contractile Dysfunction After Short-term Atrial Fibrillation Is Reduced by Verapamil but Increased by BAY K8644

Abstract: Atrial contractile dysfunction after short-term atrial fibrillation is reduced by the calcium antagonist verapamil, which suggests that transsarcolemmal calcium influx contributed to this dysfunction. The calcium agonist BAY K8644 increased postfibrillation atrial contractile dysfunction. Atrial ischemia was not observed during fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(73 citation statements)
references
References 48 publications
2
70
1
Order By: Relevance
“…Maneuvers increasing intracellular calcium (pacing, isoproterenol, and calcium) improved atrial mechanical dysfunction, suggesting an actual or relative intracellular calcium deficiency to be responsible for the observed atrial mechanical dysfunction. Previous studies have demonstrated atrial arrhythmias to result in altered calcium handling 22 and intracellular calcium accumulation, 23 perhaps implicating a supranormal intracellular calcium level for the observed effects. However, evidence suggests that homeostatic mechanisms act to reduce the accumulating intracellular calcium by a decrease of the L-type calcium current.…”
Section: Implications For the Mechanism Of Atrial Mechanical Remodelimentioning
confidence: 96%
“…Maneuvers increasing intracellular calcium (pacing, isoproterenol, and calcium) improved atrial mechanical dysfunction, suggesting an actual or relative intracellular calcium deficiency to be responsible for the observed atrial mechanical dysfunction. Previous studies have demonstrated atrial arrhythmias to result in altered calcium handling 22 and intracellular calcium accumulation, 23 perhaps implicating a supranormal intracellular calcium level for the observed effects. However, evidence suggests that homeostatic mechanisms act to reduce the accumulating intracellular calcium by a decrease of the L-type calcium current.…”
Section: Implications For the Mechanism Of Atrial Mechanical Remodelimentioning
confidence: 96%
“…Frequent [17][18][19] and irregular 20 depolarization of atrial myocytes during AF results in elevation of cytosolic calcium. 9 The absence of AF-induced contractile dysfunction in patients pretreated with verapamil suggests that AF-induced cytosolic calcium overload may mediate this acute dysfunction.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] A study of pacing-induced AF in pigs demonstrated that a brief episode of AF induces acute atrial contractile dysfunction and that this can be blunted by verapamil. 9 However, no prior studies have assessed the short-term effect of a brief episode of AF on left atrial contractility in humans or the effect of pretreatment with verapamil. Therefore, the purpose of this study was to measure the effect of pacing-induced AF on the LAA emptying velocity in patients and to determine whether verapamil modifies this effect.…”
mentioning
confidence: 99%
“…While ionic remodeling (3)(4)(5) as well as changes in cellular and structural architecture (6) have been described, increasing evidence for a role of perturbations in energetic metabolism exists. In fact, various studies have shown modifications in energetic metabolism in both animal models (7)(8)(9)(10)(11) and humans (12)(13)(14) and after both chronic or short episodes of AF (9,10,(12)(13)(14). However, a variety of changes have been observed.…”
Section: Introductionmentioning
confidence: 99%